Thermal, mechanical and morphological study of carbon nanotubes-graphene oxide and silver nanoparticles based polyurethane composites. (10th May 2019) - Gedam, Sandhya S; Chaudhary, Ashutosh Kr; Vijayakumar, R P; Goswami, A K; Bajad, Ganesh S; Pal, Dharm
Abstract: Polyurethane composite foams were prepared by solvent casting method with the addition of carbon nanotubes—graphene oxide and silver nanoparticles. Changes in micro-structural phases of the polymers were analyzed by x-ray diffraction (XRD). Morphological changes in polyurethane foams after dispersion of nanofillers were analyzed by using Field emission Scanning Electron Microscope (FESEM). Fourier Transform Infrared Spectroscopy (FTIR), XRD and FESEM analysis have confirmed the successful incorporation of nanotubes and nanoparticles into the polymer matrix. Further, TGA (Thermo-gravimetric analysis) analysis showed an increase in thermal stability of hybrid composite foam. The addition of nanofillers in the polyurethane foam has increased the tensile strength by 323%. Hybrid foam was conductive in nature and the conductivity is 2 × 10 −4 S cm −1 .